Impacts of environmental policy uncertainty on urban environmental pollutant emissions in China: a study based on textual analysis - Li, Rongda; He, Jing (Frontiers in Environmental Science, 2023)
Studies mainly focuses on measuring the economic policy uncertainty in different countries. However, few studies have focused on the construction of the environmental policy uncertainty index (EPUI). This paper selects 460 newspapers from the China National Knowledge Infrastructure (CNKI) newspaper database from 2001 to 2016, and uses the text analysis method to directly construct the national, provincial, and prefecture-level EPUI of China. We have analyzed the distribution and fluctuation trend of the EPUI, and use two-way fixed effect model with panel data to investigate the impact of environmental policy uncertainty on environmental pollutant emissions at the city level. An important discovery has been made through our research, indicating that the rise in environmental policy uncertainty is likely to result in a reduction of pollutant emissions such as urban industrial sulfur dioxide and carbon dioxide. However, this reduction comes at a cost to the promotion of the development of urban secondary industry. The Chinese EPUI constructed for the first time in this article provides significant basic data for research in the environment and energy fields, and also provides important empirical evidence for achieving China’s carbon peak and carbon neutrality goals.